Risk Factors Associated With Renal and Urinary Tract Anomalies Delineated by an Ultrasound Screening Program in Infants - Liu, Yuling; Shi, Hua; Yu, Xiaojing; Xiang, Tianchao; Fang, Ye; Xie, Xian; Pan, Xiaofen; Li, Xiaolin; Sun, Zhicai; Zhang, Bihong; Fu, Simao; Rao, Jia (Frontiers in Pediatrics, 2022)
Objective To evaluate the value of ultrasound screening for congenital anomalies of the kidney and urinary tract (CAKUT) during the early postnatal period. Methods This is a prospective study that enrolled all neonates born from August 2019 to July 2020 at one medical center. Postnatal ultrasound screening was conducted in all neonates at 1, 3, and 6 months old, respectively. Information on antenatal detection and pregnancy was collected. We performed logistic regression analyses and established a predictive model to assess the potential risk factors of abnormal ultrasound screening results. Results Postnatal ultrasound scanning in 4,877 infants identified 268 cases (5.5%) of anomalies of kidney and urinary tract by primary screening and 92 cases (1.9%) by tertiary screening. A specific diagnosis was identified in 47 cases within the 6-month screening and follow-up program. Logistic regression revealed that preterm birth, oligohydramnios, antenatal ultrasound screening anomalies, and gestational hypothyroidism were independent risk factors for the early detection of CAKUT by postnatal ultrasound screening. The above factors were adopted to develop a predictive model that showed good calibration in predicting ultrasound findings of CAKUT. Decision curve analysis demonstrated good clinical utility. Conclusions Postnatal ultrasound screening should be conducted in infants with risk factors associated with CAKUT. Further study on prenatal and fetal factors could help establish the predictive model for the early detection of CAKUT.